A new species and subgenus of Pachylaelaps Berlese from Turkey (Acari: Pachylaelapidae) - Özbek, Hasan Hüseyin; Mašán, Peter (Zootaxa, 2018)
This paper reports on three interesting species of the mite family Pachylaelapidae from Turkey (Acari: Mesostigmata). A new subgenus Longipachys Mašán & Ӧzbek, subgen. nov., with type species Pachylaelaps (Longipachylaelaps) anatolicus Ӧzbek, is erected in the genus Pachylaelaps Berlese. The description of P. anatolicus is extended to include females and males found in leaf litter in various habitats. A new species Pachylaelaps (Pachylaelaps) armiger sp. nov. is described, and compared with related species that have a polydentate chelicera. Pachylaelaps (Pachylaelaps) evansi Costa, 1971, a species previously reported from Israel, is recorded in Turkey for the first time.